Application of Mixed Methodologies in the Production Planning of Screw Conveyors for the Flour and Pasta Food Industry - Casallo, Lucy (2022)
The continuous growth of the food industry has consequently brought the need for equipment, parts, and pieces to meet the local market demand. One of these parts has a higher demand in the market, which are the screw conveyors of stainless steel 304; these are one of the components that have greater use of hours machines. For this reason, it is required to plan maintenance and repairs in the industry of reference. This article is focused on identifying the most important failure reasons in the agribusiness supply industry; it was identified that the processes of greatest opportunity measure and assembly. These processes increase the delivery time of the final product, which failures should not increase because providing the product outside the agreed time causes high financial impact as penalties and loss of customers. The company manufactures various parts for industrial mills and has a problem with delivery delays because its current fulfilment rate is below correct. This delay causes poor distribution, lack of proper planning, and not having proper cleaning in work areas. To solve this problem, it is proposed to apply mixed tools that include standardizing work to reduce production time and redistributing workstations; and the application of MRP. The proposal shows an increase in the level of on-time delivery service, which contributes to reducing penalties.